A dual catalytic strategy by the nature of the functionalization effect as well as active species on vanadium-based catalyst for enhanced low temperature SCR - Kwon, Dong Wook; Kim, Dong Ho; Lee, Seokhyun; Kim, Jongsik; Ha, Heon Phil (ELSEVIER, 2021)
The challenge for selective catalytic reduction (SCR) of NO with NH3 is to develop a proven catalyst with satisfactory performance and sulfur resistance at low temperatures. Two types of surface reaction properties have been shown to be involved in the W-Ce (VWCeTi) and Sb-Ce (VSbCeTi) systems. That is, active species have improved catalytic activity and the decomposition of ammonium bisulfate (ABS)/ammonium sulfate (AS) by the functionalization as well as the surface reactive oxygen (surface lattice oxygen/highly dispersed oxygen). The Sb-Ce system resulted in greater catalyst surface functionalization, generated the bulk-like cerium sulfate species and improved the active site by the sulfate effect. This system promoted the release of more reactive oxygen and surface lattice oxygen by enhancing the interaction between Sb and Ce to form more active species, which was found to have a positive effect on catalytic ABS/AS decomposition.